Genetic dynamics and molecular epidemiology of Salmonella typhi - Thong, Kwai Lin; Nair, S.; Subramaniam, G.; Puthucheary, S.D.; Yassin, R.M.; Cheong, Y.M.; Liu, S.L.; Sanderson, K.E.; Cordano, A.M.; Pang, T. (1999)
A large number of S. typhi isolates from various geographic regions, representing sporadic, outbreak, and environmental isolates, as well as isolates from fatal and non-fatal cases of typhoid fever have been analysed by pulsed-field gel electrophoresis (PFGE) with restriction endonucleases XbaI, SpeI, AvrII, and CeuI. The main conclusions are: (1) significant genetic diversities exist among these isolates; (2) outbreak isolates are more homogeneous compared to sporadic isolates; (3) there is movement of certain PFGE types among the countries in South-East Asia; (4) environmental isolates also show diversity and share PFGE types with clinical strains, there appear to be a correlation between PFGE pattern and isolates from fatal disease; (6) limited diversity exists in a region where typhoid fever is a recent introduction; (7) there is significant diversity in total genome size; (8) genomic arrangements within the rrn operon has occurred among many of these strains. Our findings emphasize the genomic plasticity of S. typhi and it is likely that this is closely related to the pathogenic potential and virulence of this organism.